(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The research aimed to investigate the attitudes of university girls in the Department of Sociology at Damascus University towards marrying criminals. And to measure the differences between the average scores of the research sample members according to the research variables: (family economic level, place of residence, work). The research sample consisted of (142) female students from the Department of Sociology at the Faculty of Arts and Humanities at Damascus University. The scale of young women’s attitudes towards marriage was applied to them. The research relied on the descriptive analytical approach. To verify the research hypotheses, the arithmetic means and standard deviation were calculated and the (t-test) and the one-way analysis of variance (ANOVA) test were used to indicate the significance of the differences. The research concluded with the following results: The attitude of university girls in the Department of Sociology at Damascus University towards marrying criminals was low, and there were no statistically significant differences between the average scores of the research sample members according to the research variables: (family economic level, place of residence, work).